(untitled) (Bioagro, 2022)
Due to the importance of rice (Oryza sativa) in human nutrition and its recurrent use in agricultural research, high precision of the experiments is required to detect the effects of the various alternatives to improve the production levels, and one of these primary and fundamental factors is the appropriate size of the experimental plots. In this context, this study was developed in order to establish the dimensions of the experimental plot for rice trials in an agricultural area of ​​Ecuador. A uniformity experiment 31.7 m wide by 32.0 m long was established, with a 1 m edge effect, and in which, 990 basic units of 0.9 m2 were demarcated, making combinations of 1x1 m up to 10x8 m. The sowing was by transplantation at 25 cm x 30 cm, placing eight tillers per site, and the husk grain yield was assessed. The coefficient of variation for the different combinations was obtained, the maximum curvature method was applied and a multiple regression model was defined. Likewise, soil heterogeneity was verified using Smith’s law of variances, and Fisher’s F test as support for the maximum curvature method. A suitable plot size (useful plot) of 6 m2 was determined, with dimensions of 2 m x 3 m, within experimental plots of 20 m2.